자기수용과 가족용서가 가족응집력에 미치는 영향: 성별의 조절효과 - 신선화; 정구철; Shin, Sun-Hwa; Jeong, Goo-Churl (한국콘텐츠학회 논문지, 14(3), 2014)
The purpose of this study was to identify the moderating effect of gender among self-acceptance, family forgiveness and family cohesion. It was conducted to measure self-acceptance, family forgiveness and family cohesion from 376(188 male, 188 female) university students. The moderating effect according to gender was analyzed through hierarchical regression analysis and path analysis. As a result of analysis, first, there were positive relationship, among self-acceptance, family forgiveness and family cohesion. Second, self-acceptance and family forgiveness had a significant effect on the family cohesion. Third, gender had moderating effect within the relationship of self-acceptance, family forgiveness and family cohesion. Specifically, impact on family cohesion of self-acceptance is greater in men, and impact on family cohesion of family forgiveness is greater in women. Implications of these results were explored in relation to the importance of self-acceptance and forgiveness that could be taken to improve family cohesion. In addition, this implication and suggestions for future research are provided. 본 연구는 대학생들의 자기수용과 가족용서가 가족응집력에 미치는 영향에서 성별의 조절효과를 검증하기 위해 수행되었다. 이를 위해 서울시에 소재한 1개 대학교의 대학생 376명(남자 188명, 여자 188명)을 대상으로 조사하였으며, 성별에 따른 조절효과는 위계적 회귀분석과 경로분석을 통해 분석하였고, 단순주효과검정은 분산분석을 수행한 후 도식으로 제시하였다. 연구결과, 자기수용과 가족용서, 가족응집력 간에 모두 유의한 정적 상관관계가 나타났고, 자기수용과 가족용서는 가족응집력에 유의한 정적 영향을 미치는 것으로 나타났다. 자기수용 및 가족용서와 가족응집력 간의 관계에서 성별의 조절효과는 통계적으로 유의하였다. 구체적으로 자기수용이 가족응집력에 미치는 영향은 남자가, 가족용서가 가족응집력에 미치는 영향은 여자가 더 큰 것으로 나타났다. 이러한 연구결과를 바탕으로 가족관계의 증진을 위한 자기수용과 가족용서에 대한 시사점 및 후속연구에 대한 제언을 논의하였다.